2020
DOI: 10.26555/ijain.v6i2.502
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint recognition based on shark smell optimization and genetic algorithm

Abstract: Fingerprint recognition is a dominant form of biometric due to its distinctiveness. The study aims to extract and select the best features of fingerprint images, and evaluate the strength of the Shark Smell Optimization (SSO) and Genetic Algorithm (GA) in the search space with a chosen set of metrics. The proposed model consists of seven phases namely, enrollment, image preprocessing by using weighted median filter, feature extraction by using SSO, weight generation by using Chebyshev polynomial first kind (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Entropy is use to assessment the amount data of an image and to contrast the difference of data of plain media and Stego media. Table (1) shows the results of the measures that were applied on five images in evaluating the proposed system. The results proved the strength and effectiveness of the proposed system The effectiveness of the suggested approach is contrasted with another approaches [43,44,45,46,47] in idioms of capacity and PSNR on 'Lena', 'Baboon', 'Pepper'' images which have been outlined in table 2 and figure (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entropy is use to assessment the amount data of an image and to contrast the difference of data of plain media and Stego media. Table (1) shows the results of the measures that were applied on five images in evaluating the proposed system. The results proved the strength and effectiveness of the proposed system The effectiveness of the suggested approach is contrasted with another approaches [43,44,45,46,47] in idioms of capacity and PSNR on 'Lena', 'Baboon', 'Pepper'' images which have been outlined in table 2 and figure (4).…”
Section: Resultsmentioning
confidence: 99%
“…With the fast development of internet and technology life [1] and advancement of image purports, the difficulty of protecting secrecy of such purports through the network has become a main apprehension in the recent years. Using effective image retrieval techniques, the intruders constantly attempt to access relevant image content [2] before launching a surprise attack using image malware [3,4].So, the field of data and multimedia secrecy has become very important and the field of its applications is extending [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several [14] an effective associative rule that used the genetic algorithm for predicting three different diseases which were diabetes, breast-cancer, and heart have been modeled. The main inspiration for using the genetic algorithm [15], [16] was to discover predictive rules that were highly understandable and given high predictive accuracy. The outcomes indicated that most of the classifier rules predicted heart disease with the highest accuracy which was 98% when compared with diabetes and breast-cancer accuracy which were 82% and 84.8%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fast technology development and automated life elevated the prerequisite for an additional security level. All over the globe, security is a growing requisite because a lack of security can result in great damage [1], [2]. The internet and technology are enhanced rapidly day by day.…”
Section: Introductionmentioning
confidence: 99%